Kesinambungan Program Promosi Kesehatan Rumah Sakit (PKRS) Dalam Promosi Kesehatan Berbasis Komunitas Di RSUD Ahmad Syafii Maarif - Vesdiana Vesdiana; Agung Ruhdiyat (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
The Hospital Health Promotion Program (PKRS) is an integral part of promotive and preventive efforts in health services. The success of PKRS is not only determined by the implementation of education in the hospital environment, but also by the continuity of health promotion down to the community level. This study aims to describe the implementation and continuity of community-based PKRS at Ahmad Syafii Maarif Regional General Hospital, a type C hospital. The study uses a descriptive design with a case study approach. Data were obtained through a review of PKRS program documents, activity reports, and observations of health promotion implementation. The results showed that PKRS at Ahmad Syafii Maarif Regional General Hospital had been implemented through inpatient and outpatient education, group education, the use of print and social media, and hospital-based geriatric activities in the community. The PKRS team had been formed through a director's decree and was chaired by a community nursing specialist. However, the continuity of health promotion in the community still faces obstacles in the form of limited human resources and budget, as well as suboptimal follow-up after education. The conclusion of this study emphasizes that the continuity of community-based PKRS requires strengthening the role of community nursing, hospital management support, and cross-sector collaboration so that health promotion can have a sustainable impact.